Low-volatility high-performance environment-friendly insulating resin and preparation method thereof
By using deionized water, composite crosslinking agents and functional chlorite in insulating resins, combined with UV light curing technology, the problems of insufficient environmental friendliness, high temperature resistance and wear resistance of traditional insulating resins are solved, and high quality is achieved The performance and the preparation of environmentally friendly insulating resins have significantly improved the safety and service life of power equipment.
Patent Information
- Application Number
- CN202411866284.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional insulating resins are unfriendly to the environment, have insufficient high temperature resistance and wear resistance, and are difficult to meet the needs of use in various environments. Especially in the power electronics field, softening deformation, mechanical wear and aging are prone to problems, affecting the safety and reliability of the equipment.
Using low-volatilization deionized water as diluent, composite crosslinking agent and functional chlorite, the high temperature and wear resistance of the insulating resin are enhanced through double bonds and fluorene ring structures, and the surface modification of ferulic acid is improved. Improve anti-aging ability, form a three-dimensional mesh structure and synergistic effect, and prepare high-performance insulating resins in combination with UV light curing technology.
It realizes low volatile, high performance and environmentally friendly insulating resin, significantly improves high temperature resistance, wear resistance and aging resistance, extends service life, enhances the safety and reliability of power equipment, and reduces circuit short circuits and fire risks.
Smart Images

Figure CN119306896A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating resins, and in particular to a low-volatile, high-performance, environmentally friendly insulating resin and a preparation method thereof. Background Art
[0002] In many fields such as power electronics, insulating materials play a vital role as core components that ensure the safe operation of equipment and affect product reliability. Insulating resins are an important component of insulating materials, and their performance is directly related to the stability of the entire power system and the safety of use. However, traditional insulating resins often use toluene as a diluent, which is not environmentally friendly and does not conform to the concept of environmental protection. At the same time, traditional insulating resins have general high temperature and wear resistance and poor aging resistance. When used in the field of power electronics, facing long-term high temperature environments, insulating materials will soften and deform during use. In dynamic or friction-frequent power application scenarios, traditional insulating materials are susceptible to mechanical wear, resulting in thinning or even damage to the insulating layer, making it difficult to ensure the safety of power equipment use, and increasing the risk of circuit short circuits or even fires. In the long-term use or storage process, traditional insulating materials age quickly, and have short storage and service life, so they are difficult to adapt to the long-term use needs of power projects.
[0003] The patent with announcement number CN118421052B discloses a high-insulation flame-retardant epoxy resin composition and a preparation method thereof. Vinyl benzoxazine is obtained by mixing a phosphate intermediate, 3-vinylaniline, polyformaldehyde, and toluene, and then a flame retardant is obtained by mixing vinyl benzoxazine with vinyl nano-alumina. A phosphorus-containing polyurethane prepolymer, epoxy POSS, and 2-ethyl-4-methylimidazole are mixed to obtain a toughening agent. Then, epoxy resin E42, a flame retardant, and a photoinitiator are mixed to react, and epoxy resin E44 toughening agent and curing agent methyltetrahydrophthalic anhydride are added. After vacuum degassing, a high-insulation flame-retardant epoxy resin composite is obtained. The epoxy resin composition has excellent insulation and flame retardancy after curing, good mechanical properties and good high temperature resistance. However, the epoxy resin composition uses reagents such as toluene, polyformaldehyde, and tetrahydrophthalic anhydride, which will produce harmful emissions during production and use, is not environmentally friendly, and does not conform to the concept of environmental protection. Summary of the invention
[0004] The purpose of the present invention is to provide a low-volatile, high-performance, environmentally friendly insulating resin and a preparation method thereof, which solves the problem that ordinary insulating resins are not environmentally friendly and have high temperature resistance, wear resistance and anti-aging capabilities that need to be improved, and are difficult to meet the use requirements in various environments.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A low-volatile, high-performance, environmentally friendly insulating resin comprises the following raw materials in parts by weight: 60-80 parts of polyurethane acrylate, 12-15 parts of methacrylic acid, 10-12 parts of a composite crosslinking agent, 5-8 parts of functional chlorite, 2-5 parts of a photoinitiator, and 120-200 parts of deionized water; the composite crosslinking agent is prepared by using polycarbonate as a polymer segment and introducing double bonds and fluorene rings at both ends of the polycarbonate; the functional chlorite is prepared by surface-modifying the chlorite with ferulic acid.
[0006] Furthermore, the photoinitiator is any one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, and 2,4,6-trimethylbenzoyldiphenoxyphosphine.
[0007] Furthermore, the preparation method of the composite cross-linking agent comprises the following steps: S1: polycarbonate diol and methyl-5-norbornene-2,3-dicarboxylic anhydride are placed in propylene glycol methyl ether, p-toluenesulfonic acid is added, the temperature is raised to react, and the solvent is removed after reduced pressure distillation to obtain a carboxyl-terminated polycarbonate; S2: placing the carboxyl-terminated polycarbonate and 2-aminofluorene in ethylene glycol monomethyl ether, introducing nitrogen, adding a composite catalyst, fully mixing and stirring for 8-10 hours, collecting the product after reduced pressure distillation, and obtaining a composite crosslinking agent.
[0008] In this scheme, under the action of p-toluenesulfonic acid, the hydroxyl groups at both ends of the polycarbonate diol structure react with the anhydride groups in the methyl-5-norbornene-2,3-dicarboxylic anhydride structure to obtain a carboxyl-terminated polycarbonate, and then under the action of a composite catalyst, the carboxyl group in the carboxyl-terminated polycarbonate structure reacts with the amino group in the 2-aminofluorene structure to obtain a composite crosslinking agent. The composite crosslinking agent uses polycarbonate diol as a polymer segment matrix, introduces double bonds at both ends, and allows it to participate in the preparation process of the insulating resin, and combines the polymer segments in the composite crosslinking agent with the polymers in the insulating resin matrix material. The chain segments are entangled with each other to form a three-dimensional network structure, which enhances the compactness of the insulating resin matrix material structure. At the same time, the norbornene structure and fluorene ring introduced into its structure have excellent high temperature resistance and wear resistance, and can form a synergistic effect with the cross-linked structure produced in the matrix to jointly enhance the high temperature resistance and wear resistance of the insulating resin, so that it can meet the use requirements in a variety of environments. When used in power equipment, it can effectively reduce the softening and deformation of the insulating material under high temperature, and it has good wear resistance and is not easy to break, which can effectively improve the safety of power equipment use, prevent circuit short circuits and reduce the risk of fire.
[0009] Furthermore, in step S1, the temperature of the temperature-raising reaction is 90-95° C. and the time is 3-5 hours.
[0010] Furthermore, in step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.65-1.25:0.25-0.45.
[0011] Furthermore, the method for preparing the functional chlorite comprises the following steps: Place chlorite in deionized water, disperse it by ultrasonic for 10-15 minutes, add ferulic acid, heat to 90-95°C and stir for 6-8 hours, filter, wash and vacuum dry to obtain functional chlorite.
[0012] In this scheme, the surface of chlorite has abundant hydroxyl groups that can interact with the carboxyl groups in the ferulic acid structure to obtain functional chlorite. The functional chlorite has chlorite as the core and ferulic acid coated on its surface. The chlorite modified by ferulic acid has excellent dispersibility and compatibility in the insulating resin matrix material and can effectively enhance the wear resistance of the insulating resin. The ferulic acid coated on its surface can slow down the chain reaction caused by free radicals and effectively improve the anti-aging ability of the insulating resin, so that the aging process of the insulating material can be slowed down during long-term use or storage, and the storage and service life can be improved, so that it can meet the use requirements of long-term power engineering and have a long service life.
[0013] Furthermore, the average particle size of the chlorite is 20 μm.
[0014] A method for preparing a low-volatile, high-performance, environmentally friendly insulating resin comprises the following steps: Step 1: Mix polyurethane acrylate, methacrylic acid, composite crosslinking agent, functional chlorite, photoinitiator and deionized water at room temperature and stir for 1-1.5 hours to obtain a mixed solution; Step 2: Place the mixed liquid in a mold and irradiate with a UV lamp to perform a photocuring reaction to obtain an insulating resin.
[0015] Furthermore, in step 2, the power of the UV lamp irradiation is 360-540 mW / cm 2 , energy is 600-1000mJ / cm 2 .
[0016] Beneficial effects of the present invention: The present invention uses deionized water as a diluent for the insulating resin material matrix and uses a low-volatile solvent during production, which is environmentally friendly and in line with the concept of ecological environmental protection. At the same time, the present invention involves a composite cross-linking agent and functional chlorite in the preparation process of the insulating resin, so that the prepared insulating resin has excellent high temperature resistance, wear resistance and anti-aging ability, is highly safe to use, can meet the use requirements in various environments, and has a long service life.
[0017] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Graph showing the sedimentation rates of chlorite and functional chlorite in deionized water in the examples of the present invention. DETAILED DESCRIPTION
[0019] The preparation method of the composite crosslinking agent and functional chlorite described in the following examples and comparative examples of the present invention is as follows: 1. Preparation of composite cross-linking agent S1: 3 g of polycarbonate diol and 2.6 g of methyl-5-norbornene-2,3-dicarboxylic anhydride were placed in 80 ml of propylene glycol methyl ether, 0.5 g of p-toluenesulfonic acid was added, the temperature was raised to 90° C. for reaction for 3 h, and the solvent was removed by reduced pressure distillation to obtain a carboxyl-terminated polycarbonate; S2: 3.2 g of terminal carboxyl polycarbonate and 2.8 g of 2-aminofluorene are placed in 80 ml of ethylene glycol monomethyl ether, nitrogen is introduced, 0.65 g of dicyclohexylcarbodiimide and 0.25 g of 4-dimethylaminopyridine are added, the mixture is thoroughly mixed and stirred for 8 h, and the product is collected after reduced pressure distillation to obtain a composite crosslinking agent.
[0020] The nitrogen analysis of the carboxyl-terminated polycarbonate and the composite cross-linking agent using a CHN elemental analyzer showed that the carboxyl-terminated polycarbonate did not contain nitrogen while the nitrogen content in the composite cross-linking agent was 4.6%. The appearance of nitrogen in the composite cross-linking agent was due to the reaction between the carboxyl group in the carboxyl-terminated polycarbonate structure and the amino group in 2-aminofluorene.
[0021] The hydroxyl group in the polycarbonate diol structure is reacted with the anhydride group in the methyl-5-norbornene-2,3-dicarboxylic anhydride structure to obtain a terminal carboxyl polycarbonate, and then the carboxyl group in the terminal carboxyl polycarbonate structure is reacted with the amino group in the 2-aminofluorene structure to obtain a composite crosslinking agent. The composite crosslinking agent is applied to the preparation process of insulating resin materials. During ultraviolet light curing, the polymer chain segments in the composite crosslinking agent and the polymer chain segments in the insulating resin structure are entangled with each other to form a network structure. At the same time, the norbornene structure and the fluorene ring are introduced, which significantly enhances the high temperature resistance and wear resistance of the insulating resin material and expands its application field.
[0022] 2. Preparation of functional chlorite 2.2 g of chlorite with an average particle size of 20 μm was placed in 80 ml of deionized water, and after ultrasonic dispersion for 10 minutes, 2 g of ferulic acid was added, the temperature was raised to 90° C. and stirred for 6 hours. Functional chlorite was obtained after filtration, washing, and vacuum drying.
[0023] 5g of chlorite and 5g of functional chlorite were placed in 200ml of deionized water and ultrasonically dispersed for 30min before a sedimentation rate test. Figure 1 It can be seen that chlorite has a fast sedimentation rate in deionized water and reaches sedimentation equilibrium within 4 hours; the sedimentation rate of functional chlorite in deionized water is slow, and it reaches sedimentation equilibrium after 10 hours, and the volume fraction of chlorite is significantly smaller than that of functional chlorite. This is because the surface-modified functional chlorite has better dispersibility in deionized water, which results in a slower sedimentation rate and a higher volume fraction of functional chlorite than chlorite.
[0024] Functional chlorite is obtained by the interaction between the carboxyl group in the ferulic acid structure and the hydroxyl group on the surface of chlorite. The surface of this functional chlorite contains a large amount of small molecule antioxidants, which can not only improve the dispersibility of chlorite in the matrix material, so that it can improve the wear resistance of the insulating resin, but also fix the small molecule antioxidants on the surface of chlorite, produce an anchoring effect on the small molecule antioxidants, and effectively prevent their precipitation, so that even when used for a long time, it can also exert excellent anti-aging effects, greatly extending the service life of the insulating resin.
[0025] Example 1
[0026] Preparation of insulating resin Step 1: 60 parts of polyurethane acrylate, 12 parts of methacrylic acid, 10 parts of a composite crosslinking agent, 5 parts of functional chlorite, 2 parts of 2-hydroxy-2-methyl-1-phenylacetone, and 120 parts of deionized water were mixed and stirred at room temperature for 1 hour to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 360mW / cm 2 , energy is 600mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0027] Example 2
[0028] Preparation of insulating resin Step 1, 70 parts of polyurethane acrylate, 13 parts of methacrylic acid, 11 parts of a composite crosslinking agent, 7 parts of functional chlorite, 3.5 parts of 1-hydroxycyclohexyl phenyl ketone, and 160 parts of deionized water were mixed and stirred at room temperature for 1.2 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 450mW / cm 2 , energy is 800mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0029] Example 3
[0030] Step 1: 80 parts of polyurethane acrylate, 15 parts of methacrylic acid, 12 parts of a composite crosslinking agent, 8 parts of functional chlorite, 5 parts of 2,4,6-trimethylbenzoyldiphenylphosphine and 200 parts of deionized water were mixed and stirred at room temperature for 1.5 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 540mW / cm 2 , energy is 1000mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0031] Comparative Example 1 Preparation of insulating resin Step 1: 70 parts of polyurethane acrylate, 13 parts of methacrylic acid, 7 parts of functional chlorite, 3.5 parts of 1-hydroxycyclohexyl phenyl ketone, and 160 parts of deionized water were mixed and stirred at room temperature for 1.2 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 450mW / cm 2 , energy is 800mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0032] Comparative Example 2 Preparation of insulating resin Step 1, 70 parts of polyurethane acrylate, 13 parts of methacrylic acid, 11 parts of a composite crosslinking agent, 3.5 parts of 1-hydroxycyclohexyl phenyl ketone, and 160 parts of deionized water were mixed and stirred at room temperature for 1.2 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 450mW / cm 2 , energy is 800mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0033] Comparative Example 3 Preparation of insulating resin Step 1: 70 parts of polyurethane acrylate, 13 parts of methacrylic acid, 11 parts of carboxyl-terminated polycarbonate, 7 parts of functional chlorite, 3.5 parts of 1-hydroxycyclohexyl phenyl ketone, and 160 parts of deionized water were mixed and stirred at room temperature for 1.2 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 450mW / cm 2 , energy is 800mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0034] Comparative Example 4 Preparation of insulating resin Step 1, 70 parts of polyurethane acrylate, 13 parts of methacrylic acid, 11 parts of a composite crosslinking agent, 7 parts of chlorite, 3.5 parts of 1-hydroxycyclohexyl phenyl ketone, and 160 parts of deionized water were mixed and stirred at room temperature for 1.2 hours to obtain a mixed solution; Step 2: Place the mixed liquid in the mold and use a power of 450mW / cm 2 , energy is 800mJ / cm 2 The insulating resin is obtained by irradiating the insulating resin with a UV lamp to perform a photocuring reaction.
[0035] Performance Testing The insulating resins prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into samples that met the specifications. The tensile strength of the samples and the samples treated in an aging box at 100°C for 72 hours were tested according to the standard GB / T1040-2006 to determine the mechanical properties and anti-aging ability of the samples. The heat deformation temperature of the samples was tested according to the standard GB / T1634-2004 to determine the high temperature resistance of the samples. The wear resistance of the samples was tested using a Taber abrasion tester. The grinding wheel movement rate was set to 50 r / min, and the samples were subjected to a wear test. The initial mass of the samples and the mass after 10,000 r of wear were recorded. The wear value was calculated according to the following formula: wear value = initial mass of the sample - mass of the sample after wear. The smaller the wear value, the better the wear resistance of the sample. The specific test results are shown in the table below:
[0036] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent mechanical strength, anti-aging ability, high temperature resistance and wear resistance. In the sample prepared in Comparative Example 1, no composite cross-linking agent was added, but functional chlorite was added, and the anti-aging ability was strong, and the high temperature resistance and wear resistance were general. In the sample prepared in Comparative Example 2, no functional chlorite was added, but a composite cross-linking agent was added, and the high temperature resistance was good, the wear resistance was general, and the anti-aging ability was poor. In the sample prepared in Comparative Example 3, carboxyl-terminated polycarbonate and functional chlorite were directly added, and the high temperature resistance was good, the wear resistance was general, and the anti-aging ability was excellent. In the sample prepared in Comparative Example 4, chlorite was directly added. Although a composite cross-linking agent was also added, since the chlorite was not surface-treated, the chlorite agglomerated in the matrix material, resulting in the sample prepared in Comparative Example 4 being at a poor level in terms of mechanical properties, anti-aging ability, wear resistance, and high temperature resistance.
[0037] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0038] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A low-volatile, high-performance, environmentally friendly insulating resin, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polyurethane acrylate, 12-15 parts of methacrylic acid, 10-12 parts of composite crosslinking agent, 5-8 parts of functional chlorite, 2-5 parts of photoinitiator and 120-200 parts of deionized water; the composite crosslinking agent is prepared by using polycarbonate as a polymer chain segment and introducing double bonds and fluorene rings at both ends of the polycarbonate; the functional chlorite is prepared by surface-modifying the chlorite with ferulic acid.
2. A low-volatile, high-performance, environmentally friendly insulating resin according to claim 1, characterized in that: The photoinitiator is any one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl diphenoxyphosphine.
3. The low-volatile, high-performance, environmentally friendly insulating resin according to claim 1, characterized in that: The preparation method of the composite cross-linking agent comprises the following steps: S1: polycarbonate diol and methyl-5-norbornene-2,3-dicarboxylic anhydride are placed in propylene glycol methyl ether, p-toluenesulfonic acid is added, the temperature is raised to react, and the solvent is removed after reduced pressure distillation to obtain a carboxyl-terminated polycarbonate; S2: placing the carboxyl-terminated polycarbonate and 2-aminofluorene in ethylene glycol monomethyl ether, introducing nitrogen, adding a composite catalyst, fully mixing and stirring for 8-10 hours, collecting the product after reduced pressure distillation, and obtaining a composite cross-linking agent.
4. A low-volatile, high-performance, environmentally friendly insulating resin according to claim 3, characterized in that: In step S1, the temperature of the temperature-raising reaction is 90-95° C. and the time is 3-5 hours.
5. The low-volatile, high-performance, environmentally friendly insulating resin according to claim 3, characterized in that: In step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.65-1.25:0.25-0.
45.
6. The low-volatile, high-performance, environmentally friendly insulating resin according to claim 1, characterized in that: The preparation method of the functional chlorite comprises the following steps: Place chlorite in deionized water, disperse it by ultrasonic for 10-15 minutes, add ferulic acid, heat to 90-95°C and stir for 6-8 hours, filter, wash and vacuum dry to obtain functional chlorite.
7. A low-volatile, high-performance, environmentally friendly insulating resin according to claim 6, characterized in that: The average particle size of the chlorite is 20 μm.
8. The method for preparing a low-volatile, high-performance, environmentally friendly insulating resin according to claim 1, characterized in that: The following steps are involved: Step 1: Mix polyurethane acrylate, methacrylic acid, composite crosslinking agent, functional chlorite, photoinitiator and deionized water at room temperature and stir for 1-1.5 hours to obtain a mixed solution; Step 2: Place the mixed liquid in a mold and irradiate with a UV lamp to perform a photocuring reaction to obtain an insulating resin.
9. The method for preparing a low-volatile, high-performance, environmentally friendly insulating resin according to claim 8, characterized in that: In step 2, the power of the UV lamp is 360-540 mW / cm 2 , energy is 600-1000mJ / cm 2 .
Citation Information
Patent Citations
A high insulation flame retardant epoxy resin composition and preparation method thereof
CN118421052B
UV-curing transparent insulating ink, and preparation method and application thereof
CN105199476A
Insulating resin sheet and a printed circuit board using the insulating resin sheet
CN106912159A
Cured film and method for producing same
CN108473679A
High-temperature-resistant ferulic acid-based unsaturated resin and preparation method thereof
CN114479034A